Teacher professional quality: Counselling services with technology in Pandemic Covid-19 - Supriyanto, Agus; Hartini, Sri; Irdasari, Wahyu Nila; Miftahul, Aulia; Oktapiana, Siska; Mumpuni, Sesya Dias (Universitas PGRI Madiun, 2020)
The Covid-19 pandemic is affecting academic processes around the world and the emergence of problems in students. School counsellors have a significant role in helping problems and developing student potential through counselling services with digital technology media. This study focuses on discovering various technologies that were applied and used by school counsellors in the process of counselling services during the Covid-19 pandemic. The research method used a case study method, and a qualitative descriptive method with totally subject 20 teacher professional education alumni worked as school counsellors in various islands in Indonesia. The research instrument used an open questionnaire with distribution through google form media and descriptive qualitative data analysis. The results of the study found that asynchronous media and technology-based synchronous media were the leading alternatives for online counselling services during the Covid-19 epidemic. The use of asynchronous media with WhatsApp, Facebook, Instagram or social media, as well as synchronous media with Zoom, Webex, Google Meeting, or Hangout, can help solve problems and develop student potential. Recommendations for school counsellors to immediately adapt to the era of disruption and technology in counselling services. The following advice for the government is the administration of teacher and student welfare.